Endogean and cavernicolous beetles of the Balkans. XVI. A new, anophthalmous species of Neuraphes Thomson, 1859 (Coleoptera: Staphylinidae: Scydmaeninae) from Albania - Hlaváč, Peter; Blažej, Lukáš (Zootaxa, 2016)
Neuraphes (Pararaphes) anophthalmus sp. nov. of the tribe Glandulariini is described from Albania. The genus is for the first time recorded to include completely anophthalmous males.